2022
DOI: 10.3390/polym14142787
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin-Biomineralized Silver Nanoparticles for Enhanced Photothermal Therapy with Anti-Tumor Effect

Abstract: Silver nanoparticles as photothermal agents have the problems of low stability and low photothermal conversion efficiency. Amphiphilic daptomycin can improve the stability of silver nanoparticles, thereby improving their photothermal conversion efficiency. Herein, daptomycin-biomineralized silver nanoparticles (Dap-AgNPs) were prepared by reducing silver nitrate with sodium borohydride in the presence of daptomycin as a stabilizer and biomineralizer. The Dap-AgNPs had good solution stability and peroxidase-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…AgNPs generated photothermal effects through localized surface plasmon resonance capability. [ 55 ] All the results demonstrated that the AHA/mSF@PTHB/Ag hydrogels had a good photothermal effect due to the AgNPs and mSF@PTHB.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs generated photothermal effects through localized surface plasmon resonance capability. [ 55 ] All the results demonstrated that the AHA/mSF@PTHB/Ag hydrogels had a good photothermal effect due to the AgNPs and mSF@PTHB.…”
Section: Resultsmentioning
confidence: 99%
“…[16] In recent years, various plasmonic nanomaterials have garnered wide acceptance in the development of photothermal surfaces. [3,17,18] Although both AuNPs and AgNPs, owing to their strong plasmonic nature, have dominated the field of photothermal applications, particularly in the biomedical sector for photothermal therapeutics, [19][20][21][22][23][24] existing literatures show a bias toward the use of AuNPs in the development of transparent photothermal surfaces. However, a recent study comparing AuNPs and AgNPs for photothermal heating demonstrated that AgNPs below 20 nm in size can achieve higher temperature elevation than AuNPs.…”
Section: Introductionmentioning
confidence: 99%